Genetic divergence in respect to qualitative traits and their possible use in precision breeding programme of apple (Malus Ã— domestica) - SRIVASTAVA, K K; AHMAD, N; DAS, B; SHARMA, O C; SINGH, S R; RATHER, J A (The Indian Journal of Agricultural Sciences, 2026)
The domestic apple (Malus Ã— domestica Borkh) has been originated in western Asia, eastern Europe, and south western Siberia and presences of wild relatives revealed that Indian subcontinent have ample diversity of apple. The genetic variability and divergence were studied during 2008-10 to evaluate 88 apple accessions for 10 fruit quality traits of apple used in DUS testing as per UPOV guidelines grown at Experimental Farm of CITH, Srinagar. Analysis of variance revealed the significant difference among accessions for 10 fruit quality traits. Maximum numbers of accessions(29) grouped in cluster II average fruit diameter was recorded highest (83.34 mm) in cluster II, and lowest average fruit weight was noted in cluster I. Intra cluster distance was recorded highest 1.69 in cluster II and minimum in cluster I, whereas highest inter cluster distance was noted between cluster I (6.49) and cluster II.